Pengaruh Model Think Pair Share (TPS) Terhadap Kemampuan Berpikir Kritis Materi Statistika - Fhela Vhantoria Ningrum; Wandita Rahmadanti; Muinah (Eksponen, 2025)
The fact of the problem of low critical thinking skills of students is 65.49% in accordance with the provisions of the KKM which is 70. In addition, from the results of observations obtained students are less able to analyze ideas to solve a problem. In addition, students are reluctant to do practice questions that would enable students to be competent in determining strategies and conclusions in solving questions. One of the models indicated as being able to overcome the problem of low critical thinking skills in statistical material is the TPS Model. The study aims to determine whether there is an effect of the TPS model on the critical thinking skills of statistical material for class VII students of SMP Negeri 3 Kotabumi, North Lampung in the 2023/2024 Academic Year. This research method is quantitative experimental with a quasi-experimental design. The form of quasi-experimental chosen is nonequivalent control group design. Then samples were taken from two classes, namely one class VII D for the experimental class using the TPS model and one class VII C using the model commonly used by teachers. The results of data analysis using the t-test, obtained tcount = 3.102 and ttable 1.990 then tcount> ttable so that H0 is rejected, and Ha is accepted. This means that there is an influence of the TPS model on the critical thinking skills of statistical material for class VII students of SMP Negeri 3 Kotabumi